Kenya Economic Update, December 2017 : Poised to Bounce Back? - World Bank Group (World Bank, Nairobi, 2017)
This is a critical time for Kenya, as the incoming administrations at national and devolved levels face the high expectations of ordinary Kenyans to deliver on ambitious economic development agendas and hasten the attainment of Vision 2030. This sixteenth edition of the Kenya economic update seeks to contribute to the policy discourse on pertinent economic issues. The Kenyan economy faced multiple headwinds in 2017. A drought in the earlier half of the year, the ongoing slowdown in private sector credit growth, and a prolonged election cycle weakened private sector demand, notwithstanding an expansionary fiscal stance. Nonetheless, reflecting the relatively diverse economic structure, these headwinds were partially mitigated by the recovery in tourism, better rains in the second half of the year, still low global oil prices, and a relatively stable macroeconomic environment. With headwinds subsiding, economic growth is projected to rebound over the medium term, reaching about 5.8 percent in 2019. However, this rebound is predicated on policy reforms needed to address downside risks that have the potential to derail medium term prospects. This report presents a rich menu of policy options tabled in this edition of the Kenya Economic Update, identifying opportunities for the consolidation of the fiscal stance, both from an expenditure and revenue mobilization perspective. This is complimented with specific suggestions of macroeconomic and microeconomic reform measures that could help address the slowdown in credit growth and the broader issue of access to credit. Finally, policy options to climate proof the agriculture sector, to mitigate the worse effects of adverse weather conditions are discussed.